2013
DOI: 10.1371/journal.pone.0057523
|View full text |Cite
|
Sign up to set email alerts
|

Wee1 Inhibition by MK-1775 Leads to Tumor Inhibition and Enhances Efficacy of Gemcitabine in Human Sarcomas

Abstract: Sarcomas are rare and heterogeneous mesenchymal tumors affecting both pediatric and adult populations with more than 70 recognized histologies. Doxorubicin and ifosfamide have been the main course of therapy for treatment of sarcomas; however, the response rate to these therapies is about 10–20% in metastatic setting. Toxicity with the drug combination is high, response rates remain low, and improvement in overall survival, especially in the metastatic disease, remains negligible and new agents are needed. Wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 38 publications
4
68
0
Order By: Relevance
“…Endonuclease-mediated cleavage of chicken-foot DNA structures associated with stalled replication forks then leads to replication associated DNA double-strand breaks (25). Consistent with this model, MK-1775 monotherapy is associated with induction of pan-nuclear γH2AX staining in this current report and several other studies, and a similar phenotype is seen with Wee1 siRNA (7, 2022). Interestingly, Myc overexpression is associated increased replicative stress (26, 27), and the highly sensitive GBM22 xenograft line from this study harbors high level Myc amplification (unpublished data).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Endonuclease-mediated cleavage of chicken-foot DNA structures associated with stalled replication forks then leads to replication associated DNA double-strand breaks (25). Consistent with this model, MK-1775 monotherapy is associated with induction of pan-nuclear γH2AX staining in this current report and several other studies, and a similar phenotype is seen with Wee1 siRNA (7, 2022). Interestingly, Myc overexpression is associated increased replicative stress (26, 27), and the highly sensitive GBM22 xenograft line from this study harbors high level Myc amplification (unpublished data).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the presence of replicative stress in this model, GBM22 cells are highly aneuploid and exhibited marked basal elevation in γH2AX staining that was further accentuated with MK-1775 treatment. In a neurosphere assay, which provides results similar to a clonogenic assay and is generally more sensitive than the CyQuant assay for assessment of cytotoxicity, GBM22 cells (IC 50 of 12 nM; Figure 1C) were exquisitely sensitive to single agent MK-1775 as compared to previously published studies in sarcoma and neuroblastoma with IC 50 s ranging from 100 to over 1000 nM (7, 9, 22). In a transgenic model of neuroblastomas, homozygous expression of the MYCN oncogene was associated with an almost 3 fold-reduction in IC 50 (62 nM) as compared to heterozygous expression of MYCN (161 nM) (9).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…It has been shown that unscheduled mitosis results in micro-nuclei formation and apoptosis in tumor cells treated with gemcitabine and MK-1775 (32, 33). Therefore, we tested whether sensitization of the isogenic PCI-13 cells to cisplatin by addition of MK-1775 led to apoptosis induction.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, inhibition of checkpoint kinases in combination with DNA damaging agents may become a therapeutic strategy for the treatment of various malignancies. [15][16][17][18] Histone deacetylase (HDAC) inhibitors (HDACIs) have demonstrated anticancer activity in numerous malignancies including AML. [19][20][21][22][23][24][25][26] They have been demonstrated to induce cell cycle arrest, differentiation, and apoptosis in cancer cells, but less so in normal cells.…”
Section: Introductionmentioning
confidence: 99%